Is that right? : critical thinking and the social world of the young learner - Wright, Ian, 1941- (Pippin teacher's library., 2002)
Annotation What could be a better moment than today to teach our children the value and rewards of critical thinking? Maybe, but when Ian Wright began this book, believing strongly that the younger the learner the more valuable and rewarding the lesson, he became concerned by his inability to find much available of a systematic nature to help a teacher; what he did find seemed all too often confusing because of differing notions of critical thinking and of how to teach it. So he wrote in the hope that he could somehow help to provide the motivation, background knowledge and the skills needed to teach our young people how to begin to become critical thinkers. While Is That Right? Critical Thinking and the Social World of the Young Learner -- which defines critical thinking as the ability to make reasoned judgements in problematic situations -- can be applied to all subject areas, Ian has chosen for practical reasons to focus on the social dimensions of our young peoples' lives. Nevertheless, the ideas on thinking critically about empirical, conceptual and value claims can obviously be readily adapted to all subject areas.